The Attenuated Brucella abortus Strain 19 Invades, Persists in, and Activates Human Dendritic Cells, and Induces the Secretion of IL-12p70 but Not IL-23. - Mario Weinhold; Martin Eisenblätter; Edith Jasny; Michael Fehlings; Antje Finke; Hermine Gayum; Ursula Rüschendorf; Pablo Renner Viveros; Verena Moos; Kristina Allers; Thomas Schneider; Ulrich E Schaible; et al. (PLoS ONE)
Background Bacterial vectors have been proposed as novel vaccine strategies to induce strong cellular immunity. Attenuated strains of Brucella abortus comprise promising vector candidates since they have the potential to induce strong CD4(+) and CD8(+) T-cell mediated immune responses in the absence of excessive inflammation as observed with other Gram-negative bacteria. However, some Brucella strains interfere with the maturation of dendritic cells (DCs), which is essential for antigen-specific T-cell priming. In the present study, we investigated the interaction of human monocyte-derived DCs with the smooth attenuated B. abortus strain (S) 19, which has previously been employed successfully to vaccinate cattle. Methodology/principal findings We first looked into the potential of S19 to hamper the cytokine-induced maturation of DCs; however, infected cells expressed CD25, CD40, CD80, and CD86 to a comparable extent as uninfected, cytokine-matured DCs. Furthermore, S19 activated DCs in the absence of exogeneous stimuli, enhanced the expression of HLA-ABC and HLA-DR, and was able to persist intracellularly without causing cytotoxicity. Thus, DCs provide a cellular niche for persisting brucellae in vivo as a permanent source of antigen. S19-infected DCs produced IL-12/23p40, IL-12p70, and IL-10, but not IL-23. While heat-killed bacteria also activated DCs, soluble mediators were not involved in S19-induced activation of human DCs. HEK 293 transfectants revealed cellular activation by S19 primarily through engagement of Toll-like receptor (TLR)2. Conclusions/significance Thus, as an immunological prerequisite for vaccine efficacy, B. abortus S19 potently infects and potently activates (most likely via TLR2) human DCs to produce Th1-promoting cytokines.